Religious Knowledge Mediates between the Knowledge about Reproductive Health and Self-Esteem of Malaysian Adolescents - Mazlina Che Mustapa; Nasruddin Subhi; Fauziah Ibrahim; Muhammad Saleem (Journal of Islamic Thought and Civilization, 2020)
Knowledge of reproductive health among adolescents is a matter of great concern for both parents and educational institutes in Malaysia; with the development of self-esteem in Malaysian youngsters. Lack of reproductive knowledge may lead to a plethora of issues. Therefore, this study sought to quantify the mediating role of religious knowledge between the knowledge of reproductive health and self-esteem of Malaysian adolescents. The study employed a quantitative research design in which self-administered surveys were used to collect data from 400 high school students belonging to 16 hot spot schools in the Seremban district of Malaysia. Purposive sampling technique was used to select 25 students from each school. Regression analysis revealed that the knowledge of sexuality and reproductive health have a significant impact on the self-esteem of adolescents. Furthermore, mediation analysis also exhibited the intermediary role of religious knowledge between the knowledge of reproductive health and self-esteem of Malaysian adolescents. Suggestions have been given to promote such programs in educational institutes by the ministry of education which would help to promote the reproductive health and self-esteem of Malaysian adolescents keeping in view scientific prospects of religious teachings.